Environmental Contamination and Occupational Exposure of Algerian Hospital Workers - Verscheure, Eline; Creta, Matteo; Vanoirbeek, Jeroen; Zakia, Meziane; Abdesselam, Taleb; Lebegge, Robin; Poels, Katrien; Duca, Radu-Corneliu; Godderis, Lode (Frontiers in Public Health, 2020)
Guidelines have been introduced to limit the occupational exposure to cytostatic drugs. Even though this has led to a reduction in exposure, several studies reported quantifiable concentrations of these compounds in healthcare workers. Therefore, the aim of this study was to evaluate the occupational exposure to cytostatic drugs in hospital workers from the university hospital in Tlemcen, Algeria. Monitoring was performed by collecting wipe samples from several surfaces, objects, personal protective equipment (gloves and masks) and skin in an Algerian university hospital. Wipe samples were analyzed with ultra-performance liquid chromatography coupled to a mass spectrometer. Concentrations ranged from below the limit of quantification up to 208.85 ng/cm², 23.45 ng/cm², 10.49 ng/cm² and 22.22 ng/cm² for cyclophosphamide, ifosfamide, methotrexate and 5-fluorouracil, respectively. The highest values could be observed in the oncology department. Nowadays, there are still no safe threshold limit values for occupational exposure to cytostatic agents. Therefore, contamination levels should be kept as low as reasonably achievable. In conclusion, despite the numerous guidelines and recommendations, healthcare workers are still exposed to cytostatic agents. Consequently, actions should be taken to reduce the presence of harmful agents in the work environment.